(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article highlights the importance of increasing the level of knowledge of students through STEAM (science, technology, engineering, art and mathematics) education. STEAM, a complementary and integrated unit of disciplines, helps students develop critical thinking, business knowledge, creativity and innovation. Combining science, technology, engineering, art and math, this method encourages students to take action and find alternative solutions to important social problems